The Impact of Socio-Economic and Demographic Factors on the Use of Digital Access to Financial Services - Alexander Conrad; Doris Neuberger; Florian Peters; Fabian Rösch (Credit and Capital Markets – Kredit und Kapital, 2019)
This paper investigates which socio-economic and demographic factors influence the demand for digital access to financial services. For this purpose, customer data from all public savings banks in Germany are linked with socio-economic and demographic data at regional level. As a result, attributes can be identified that promote a so-called informational divide. The risk of such a divide is comparatively high in rural, sparsely populated areas with a high average age of the population and in regions with a relatively low average formal education level. Here, people could lose access to basic financial services as a basis for economic and social participation as a result of ongoing digitisation.
Keywords: L86; O33; R12; R20; R51; G21; L32; L38; 330; digital divide; informational divide; savings banks; regional comparison; financial services; digitalisation